Bases of satellite technologies are in a geodesy. (Journal of Geography and Environmental Management, 2016)
Planned creation of state satellite geodesic network, establishment of the state system of coordinates and lack of information, to this direction does a necessity to pay attention to bases of satellite technologies in a geodesy.
Keywords: geodesy; geoinformatics; satellite geodesic network; state system of coordinates